The use of fetal fibronectin in suspected pre-term labour. (January 2014) - Anwar, A.; Lindow, S. W.; Greaves, L.; Hall, S.; Jha, R.
<x xml:space="preserve">Abstract</x> Pre-term delivery is the leading cause of neonatal mortality and morbidity. The aim of this study is to determine the diagnostic accuracy of the fetal fibronectin (FF) test in predicting pre-term birth, the test interpretation and subsequent action taken in normal clinical practice in a busy tertiary centre setting. A total of 133 symptomatic women were included in the study and underwent the FF test. The use of tocolysis and corticosteroids were significantly greater in test-positive patients (p < 0.001). A negative test for detecting pre-term delivery within 10 days of the test was 100% sensitive with 100% negative predictive value (NPV). Our study has confirmed that a negative FF is an excellent short-term test to exclude pre-term delivery. The use of FF testing in routine clinical practice results in test characteristics similar to those found in research studies. This implies that the conclusions reached by researchers can be reliably translated into clinical practice.